A taxonomy and classification of web service QoS elements. (11th February 2011) - Godse, Manish; Bellur, Umesh; Sonar, Rajendra
A key problem in service oriented computing is that of service selection. Selecting the appropriate service depends upon an understanding of two major classes of requirements: functional and quality of service (QoS). There may be multiple service providers satisfying the functional requirements with varying QoS. Thus, QoS becomes a service-differentiating criterion of selection. Choosing the service with the best match of QoS requirements is a multi-criteria decision-making problem that needs a thorough understanding of QoS. There are multiple stakeholders involved in the process of service recommendation who may have varying concerns on the QoS attributes. What is needed is a comprehensive taxonomy of QoS parameters and their relationships that can form QoS ontology of web services. In this paper, we present such ontology.